Histological Structure of Spleen White Rat (Rattus norvegicus L.) After Induced of Nanochitosan Preparation of Neem Leaf (Azadirachta indica A. Juss) Ethanol Extract - Ningtias, Putri Lestari; Suprihatih, Teguh; Sitasiwi, Agung Janika (Jurnal Sain Veteriner, 2024)
Agents of immunomodulation are compounds that have the ability to balance the immune system throughout the body. The neem plant is one of the herbal plants that is often used as traditional medicine. Neem leaves (Azadirachta indica A. Juss) contain antioxidants that have the potential to be antiinflammatory, antiviral, and as an immunomodulatory agent. The constraint in giving medicine orally is the low bioavailability of drugs and the distribution of active compounds of herbal plants. This problem can be solved by packaging herbal plant extracts in nanochitosan. The purpose of this study was to analyze the effect of induced of a nanochitosan ethanol extract of neem leaves on the histological structure of the spleen tissue of female Wistar white rats. This study used a randomized design (CRD) which was divided into 3 treatment groups with 4 repetitions. Treatments include control (P0), an ethanol extract of neem leaves 2 ml/head/day (P1), and nanochitosan preparation of neem leaves 2 ml/head/day (P2). The parameters measured were the diameter of white pulp, the diameter of germinal centre, the area of white pulp, and the area of germinal centre in the spleen. Data on the diameter and the area of the white pulp and germinal centre were analyzed statistically parametrically with ANOVA with a 95% level of confidence, if the data were not normally distributed, the Kruskall Wallis nonparametric test was carried out. Data that were significantly different were carried out by Duncan’s further test. The results showed that the treatment of nanochitosan preparations of neem leaf ethanol extract had a significant difference in the diameter of the white pulp and germinal centre as well as the area of the white pulp and germinal centre (P<0,05). The conclusion of this study was that the nanochitosan preparation ethanol extract of neem leaves at a dose of 14 mg/kg BB can increase the diameter and the area of the white pulp and germinal centre.